Operational definition of complementary, alternative, and integrative medicine derived from a systematic search - Ng, Jeremy Y.; Dhawan, Tushar; Dogadova, Ekaterina; Taghi-Zada, Zhala; Vacca, Alexandra; Wieland, L. S.; Moher, David (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Identifying what therapies constitute complementary, alternative, and/or integrative medicine (CAIM) is complex for a multitude of reasons. An operational definition is dynamic, and changes based on both historical time period and geographical location whereby many jurisdictions may integrate or consider their traditional system(s) of medicine as conventional care. To date, only one operational definition of “complementary and alternative medicine” has been proposed, by Cochrane researchers in 2011. This definition is not only over a decade old but also did not use systematic methods to compile the therapies. Furthermore, it did not capture the concept “integrative medicine”, which is an increasingly popular aspect of the use of complementary therapies in practice. An updated operational definition reflective of CAIM is warranted given the rapidly increasing body of CAIM research literature published each year. Methods Four peer-reviewed or otherwise quality-assessed information resource types were used to inform the development of the operational definition: peer-reviewed articles resulting from searches across seven academic databases (MEDLINE, EMBASE, AMED, PsycINFO, CINAHL, Scopus and Web of Science); the “aims and scope” webpages of peer-reviewed CAIM journals; CAIM entries found in online encyclopedias, and highly-ranked websites identified through searches of CAIM-related terms on HONcode. Screening of eligible resources, and data extraction of CAIM therapies across them, were each conducted independently and in duplicate. CAIM therapies across eligible sources were deduplicated. Results A total of 101 eligible resources were identified: peer-reviewed articles (n = 19), journal “aims and scope” webpages (n = 22), encyclopedia entries (n = 11), and HONcode-searched websites (n = 49). Six hundred four unique CAIM terms were included in this operational definition. Conclusions This updated operational definition is the first to be informed by systematic methods, and could support the harmonization of CAIM-related research through the provision of a standard of classification, as well as support improved collaboration between different research groups.